Dmrt1 is required for primary male sexual differentiation in Chinese soft-shelled turtle Pelodiscus sinensis - Wei Sun (Nature Portfolio, 2017)
Abstract In vertebrates, the primary sex-determining signals that initiate sexual development are remarkably diverse, ranging from complete genetic to environmental cues. However, no sex determination-related genes have been functionally identified in reptiles. Here, we characterized a conserved DM domain gene, Dmrt1, in Chinese soft-shelled turtle Pelodiscus sinensis (P. sinensis), which exhibits ZZ/ZW sex chromosomes. Dmrt1 exhibited early male-specific embryonic expression, preceding the onset of gonadal sex differentiation. The expression of Dmrt1 was induced in ZW embryonic gonads that were masculinized by aromatase inhibitor treatment. Dmrt1 knockdown in ZZ embryos by RNA interference resulted in male to female sex reversal, characterized by obvious feminization of gonads, significant down-regulation of testicular markers Amh and Sox9, and remarkable up-regulation of ovarian regulators, Cyp19a1 and Foxl2. Conversely, ectopic expression of Dmrt1 led to largely masculinized genetic females, production of Amh and Sox9, and a decline in Cyp19a1 and Foxl2. These findings demonstrate that Dmrt1 is both necessary and sufficient to initiate testicular development, thereby acting as an upstream regulator of the male pathway in P. sinensis.